2021
DOI: 10.3390/geomatics1010009
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Urban and Peri-Urban Land Cover in Zimbabwe: Challenges and Opportunities

Abstract: Accurate and current land cover information is required to develop strategies for sustainable development and to improve the quality of life in urban areas. This study presents an approach that combines multi-seasonal Sentinel-1 (S1) and Sentinel-2 (S2) data, and a random forest (RF) classifier in order to map land cover in four major urban centers in Zimbabwe. The specific objective of this study was to assess the potential of multi-seasonal (rainy, post-rainy, and dry season) S1, rainy season S2, post-rainy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…We used mean and median seasonal Sentinel-1 imagery because the imagery shows lower speckle than single-date imagery. As a result, we did not perform speckle reduction because it generally reduces spatial resolution (Kamusoko et al 2021). Note that analysis-ready Sentinel-1 data was processed and terrain corrected in GEE.…”
Section: Land Cover Mapping Labsmentioning
confidence: 99%
“…We used mean and median seasonal Sentinel-1 imagery because the imagery shows lower speckle than single-date imagery. As a result, we did not perform speckle reduction because it generally reduces spatial resolution (Kamusoko et al 2021). Note that analysis-ready Sentinel-1 data was processed and terrain corrected in GEE.…”
Section: Land Cover Mapping Labsmentioning
confidence: 99%
“…Consequently, geospatial or mapping agencies in the less developed countries fail to produce timely, reliable, and accurate geospatial information. Furthermore, official development assistance (ODA) funding for major mapping projects has declined over the past decades (Kamusoko et al 2021).…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…First, built-up areas in sparse urban or peri-urban areas appear identical to fallow cropland and bare areas because these features exhibit high reflectance in the visible-infrared wavelengths (Herold et al 2004;Schneider 2012). For example, spectral similarity between newly developed built-up areas and other land cover surfaces such as fallow cropland fields and bare areas has been reported to cause classification errors, especially in peri-urban areas in developing countries (Kamusoko et al 2013(Kamusoko et al , 2021Schug et al 2018). This is because most built-up structures in peri-urban areas are made of the same materials found in the surrounding areas, which results in low object-to-background contrast (Jensen 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, spectral-temporal features derived from multi-seasonal Sentinel-2 data can be used to discriminate built-up areas from cropland and bare areas. Past studies have shown that multi-seasonal or multi-temporal Sentinel-2 or Landsat data improve land cover mapping in urban and peri-urban areas (Kamusoko et al 2021;Yuan et al 2005). This is because built-up spectral responses are largely persistent during the different seasons, while non-built-up (e.g., cropland and bare areas) spectral responses change (Griffiths et al 2010).…”
Section: Introductionmentioning
confidence: 99%